Cultural Dimensions and The Spread of HIV/Aids in The People's Community - Lidya Melissa Bukit (Talenta Publisher, 2022)
HIV/AIDS is a disease that attacks the immune system of human body, causing weaker body in fighting infection., despite that Tanah Karo district is known as areas that living the cultural and karonese tradition . The study used qualitative explorative approach. The results show that there are different cultures and customs among Karo communities affect their sexual behavior. Rebu tradition, which is a norm that limits close interaction among different relatives, to a certain extent resulted in the omission of the attitude of his own family members that will affect the lack of prevention of HIV / AIDS. Patriarchal culture that prioritizes the interests of men, resulting in esclusion of women's voice including in the reproductive sexual issues.